2016
DOI: 10.1021/acs.jpcc.6b00133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Implantation Damage Formation in AlxGa1–xN Compounds

Abstract: Al x Ga 1−x N alloys, covering the entire compositional range (0 ≤ x ≤ 1), were implanted at room temperature with 200 keV argon (Ar) ions to fluences ranging from 1 × 10 13 to 2 × 10 16 Ar/cm 2 . The damage formation mechanisms and radiation resistance of Al x Ga 1−x N alloys were investigated combining in situ Rutherford backscattering spectrometry/channeling (RBS/C) and ex situ X-ray diffraction (XRD) in order to assess the damage profiles and the elastic response of the material to radiation. For all compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…Similar behavior of the bimodal damage was also demonstrated in Ref. [9] for Al x Ga 1-x N alloys (x = 0, 0.13, 0.47, 0.7, and 1) implanted with Ar + ions. In addition, the X-ray diffraction (XRD) analysis has shown that the implantation with Ar + ions introduces hydrostatic strain resulting from the expansion of the c-lattice parameter.…”
Section: Introductionsupporting
confidence: 85%
“…Similar behavior of the bimodal damage was also demonstrated in Ref. [9] for Al x Ga 1-x N alloys (x = 0, 0.13, 0.47, 0.7, and 1) implanted with Ar + ions. In addition, the X-ray diffraction (XRD) analysis has shown that the implantation with Ar + ions introduces hydrostatic strain resulting from the expansion of the c-lattice parameter.…”
Section: Introductionsupporting
confidence: 85%
“…Efficient dynamic annealing leads to low damage accumulation rates for low and medium fluences followed by a strong increase of damage level at higher fluences due to the formation of extended defects. 28,30,45 Lorenz et al 19 studied the relative defect density as a function of the fluence, for random and channeled implantation in AlN implanted with Eu using similar conditions as in the present study. These authors showed that for random implantation the strong increase of defect accumulation rate starts at $1 Â 10 15 Eu cm À2 while for channeled implantation this increase is delayed to fluences of $2 Â 10 15 Eu cm À2 , in agreement with our results (Figure 3).…”
Section: A Rbs/c Studiesmentioning
confidence: 81%
“…28,29 Faye et al studied the AlGaN alloys under Ar implantation and showed a four stage damage build-up process, without reaching amorphisation at saturation damage level and with higher defect levels reached for high AlN content samples. 30 In the present work, we doped Al x Ga 1-x N samples with Tm ions by ion implantation under random and channeled implantation geometries. A detailed study of the structural properties was performed with Rutherford backscattering spectrometry/channeling, transmission electron microscopy, and X-ray diffraction.…”
mentioning
confidence: 99%
“…Much less work was done on AlN (see e.g., Refs. and references therein). Both materials have in common that the concept of critical temperatures as explained in Section 2.1 does not apply.…”
Section: Group III Nitride Systemsmentioning
confidence: 99%
“…At Ar ion fluences above 1 × 10 15 cm −2 complex tangles of defect clusters and extended defects form which saturate in a second plateau (for more detailed descriptions of the microscopic processes see Ref. and references therein). Similar fluence dependences are also observed for heavier ion species .…”
Section: Group III Nitride Systemsmentioning
confidence: 99%